2017
DOI: 10.1016/j.socscimed.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Geographic mobility and potential bridging for sexually transmitted infections in Agbogbloshie, Ghana

Abstract: Short-term mobility can significantly influence the spread of infectious disease. In order for mobile individuals to geographically spread sexually transmitted infections (STIs), individuals must engage in sexual acts with different partners in two places within a short time. In this study, we considered the potential of mobile individuals as bridge populations – individuals who link otherwise disconnected sexual networks and contributed to ongoing STI transmission. Using monthly retrospective panel data, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…This requires research to reveal the global burden of the disease [4]. Previous studies on STIs in sub-Saharan African countries have focused on the region as a whole [4] and on specific countries such as Ghana [5][6][7] and Ethiopia [2]. Such studies have identified religion, mass media exposure, and having multiple partners as predictors of STIs.…”
Section: Introductionmentioning
confidence: 99%
“…This requires research to reveal the global burden of the disease [4]. Previous studies on STIs in sub-Saharan African countries have focused on the region as a whole [4] and on specific countries such as Ghana [5][6][7] and Ethiopia [2]. Such studies have identified religion, mass media exposure, and having multiple partners as predictors of STIs.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and context of migrant sexual networks are critical for understanding risks of HIV transmission and the effectiveness of prevention interventions: the location (place) and timing of sexual ties can interrupt or dilute the effectiveness of interventions such as UTT. Migrant networks can bridge otherwise separate places and contribute to ongoing HIV transmission by engaging in sex acts in different places or maintaining relationships with sexual partners who live in different places . The reverse is also possible, but less examined: migration can bridge places with different UTT coverage and interrupt the effectiveness of interventions.…”
Section: Sexual Networkmentioning
confidence: 99%
“…age, race/ethnicity) . Sexual partners of mobile individuals may also be migrants or people living outside their home community (assortative mixing by migration status) . Therefore, a migrant's partners may lack exposure to the same level of HIV treatment and prevention, and thus have higher rates of HIV infection.…”
Section: Sexual Networkmentioning
confidence: 99%
“…Individuals in the core group tend to recruit new sexual partners into their network periodically, particularly when they change their geographic residence (Aral, 2000;Stratford et al, 2000;Lichtenstein et al, 2008;Cassels et al, 2017). Few studies have identified this pattern in truck drivers, commercial sex workers and migrant labourers (Stratford et al, 2000;Lichtenstein et al, 2008;Nguyen et al, 2009;Neaigus et al, 2016;Cassels et al, 2017).…”
Section: Introductionmentioning
confidence: 99%